Political Participation, Civic Education, and Social Media on Generation Z's Political Engagement - Suhariyanto, Didik; Rozak, Abdul (The Eastasouth Journal of Social Science and Humanities, 2025)
This study aims to investigate the influence of political participation, civic education, and social media on the political engagement of generation Z in Indonesia. Using a survey method, data were collected from 500 respondents consisting of college and high school students aged 18 to 24 years. Multiple regression analysis was conducted to identify the relationship between independent variables and political engagement. The results showed that all three variables had a significant influence, with civic education and social media use contributing positively to the level of political engagement. These findings indicate the importance of developing educational programs that emphasize civic education and the use of social media as a tool to encourage political participation among the younger generation. This study suggests that educational institutions and the government should work together to create an environment that supports the political engagement of generation Z.